Endometrial safety and bleeding profile of a 17β-estradiol/progesterone oral softgel capsule (TX-001HR)*. Issue 4 (April 2020) - Mirkin, Sebastian; Goldstein, Steven R.; Archer, David F.; Pickar, James H.; Graham, Shelli; Bernick, Brian
Abstract: Objective: The aim of the study was to evaluate the effect of a single-capsule 17β-estradiol/progesterone (E2/P4), TX-001HR, on endometrial safety, to report on amenorrhea and bleeding patterns of users, and to identify predictors of amenorrhea. Methods: The REPLENISH trial (NCT01942668) evaluated use of TX-001HR in menopausal women (40-65 y) with vasomotor symptoms (VMS) and a uterus. Women were randomized to daily E2/P4 (mg/mg: 1/100, 0.5/100, 0.5/50, or 0.25/50), or placebo for 12 months. Incidence rate of endometrial hyperplasia was calculated from endometrial biopsies conducted at screening and study completion. Women reported bleeding and spotting in daily diaries. The number of bleeding and/or spotting days and the proportion of women with no bleeding or amenorrhea were compared between treatment and placebo using the Fisher exact test. Predictors of cumulative amenorrhea were assessed by univariate analyses. Results: Women ( n = 1, 835) who took at least one study dose comprised the safety population; 1, 255 had baseline and 12-month biopsies and comprised the endometrial safety population. Incidence of endometrial hyperplasia was ⩽0.36% with any dose of TX-001HR after 1 year of use (one-sided upper 95% confidence interval ⩽4%). Cumulative amenorrhea (no bleeding/spotting) rates increased over time and were relatively high from cycle 1 to 13 with TX-001HR (56%-73%; placebo 79%; P < 0.05 except with 0.25/50 dose). Few vaginal bleeding adverse events (1.0%-4.6% TX-001HR vs 0.7% placebo) were reported and discontinuations due to bleeding were low (0.4%-1.4% vs 0%). Cumulative amenorrhea was significantly more frequent in older women, those further from their last menstrual period, and those with lower baseline E2 concentrations (all; P < 0.01). Conclusions: All doses of TX-001HR provided endometrial protection and were associated with an improved bleeding profile over time; older age, further last menstrual period, or lower baseline E2 may predict amenorrhea with TX-001HR.